Future Information Technology FutureTech 2013 - Park, James J. (Jong Hyuk).; Stojmenovic, Ivan.; Choi, Min.; Xhafa, Fatos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Future technology information technology stands for all of continuously evolving and converging information technologies, including digital convergence, multimedia convergence, intelligent applications, embedded systems, mobile and wireless communications, bio-inspired computing, grid and cloud computing, semantic web, user experience and HCI, security and trust computing and so on, for satisfying our ever-changing needs. In past twenty five years or so, Information Technology (IT) influenced and changed every aspect of our lives and our cultures. These proceedings foster the dissemination of state-of-the-art research in all future IT areas, including their models, services, and novel applications associated with their utilization.
Dedicated Smart Software System for Mobile X-ray; Chang Won Jeong, et al -- Real-time Intuitive Terrain Modeling by Mapping Video Images onto a Texture Database; Wei Song, et al -- The RIP for Random Matrices with Complex Gaussian Entries; Kuo Xu, et al -- Evolving Mobile App Recommender Systems: An Incremental Multi-objective Approach; Xiao Xia, et al -- Projects Proposals Ranking; Sylvia Encheva -- A Stereo Micro Image Fusion Algorithm Based on Expectation-Maximization Technique; Cuixia Bai, et al -- Moldable Job Scheduling for HPC as a Service; Kuo-Chan Huang, et al -- MapReduce Example with HBase for Association Rule; Jongwook Woo, Kilhung Lee -- Service Level Agreement Renegotiation Framework for Trusted Cloud-based System; Ahmad Fadzil M Hani, et al -- A cross-IdP single sign-on method in SAML-based architecture; Tzu-I Yang, et al -- Live Virtual Machine Migration with Optimized Three-Stage Memory Copy; Feiran Yin, et al -- Performances of New Chaotic Interleaver Design in OFDM-IDMA System; Brahim AKBIL, Driss ABOUTAJDINE -- Application of an artificial intelligence method for diagnosing acute appendicitis: The support vector machine; Sung Yun Park, et al.
Keywords: Engineering; Information systems; Multimedia systems; Telecommunication; Engineering; Communications Engineering, Networks; Information Systems and Communication Service; Multimedia Information Systems